Endovascular Management of Pancreatitis-Related Hemorrhage: Single-Center Experience - Sunil Kumar; Jagadeesh R. Singh; Mahesh T. Kumar; K.N. Nagbhushan; Nageshwar D. Reddy; G.V. Rao (Journal of Clinical Interventional Radiology ISVIR)
Purpose The main purpose of this article is to assess the outcomes of endovascular management of pancreatitis-related hemorrhage. Materials and Methods Retrospective analysis of patients referred for endovascular management of pancreatitis-related bleeding from January 2010 to December 2017 was performed. Patients’ demographics, clinical presentation, etiology, laboratory findings, angiography findings, details of the endovascular procedure, technical outcome, clinical outcome, and complications were assessed. Results One hundred and five patients with a mean age of 37 years were included in this study. Splenic artery (41.7%) was the most commonly involved vessel. Middle colic, left colic, superior mesenteric, jejunal, left inferior phrenic, and left renal subcapsular arteries were the less commonly involved vessels. Embolization was performed using coils in 72 (68.5%) patients, n-butyl cyanoacrylate (n-BCA) in 21 (20%) patients, both coil and n-BCA in 8 (7.6%) patients, and 4 (3.8%) patients underwent stent graft placement. Technical success was achieved in 98% (n = 103) and clinical success in 93.2% (n = 96) of patients. Rebleeding was seen in 6.8% (n = 7) of patients. Six patients with rebleeding were managed by reintervention. Four patients had rebleeding from the same vessel, and two patients had rebleeding from a different vessel. One patient died due to massive rebleeding. Minor complications were seen in 14.2% (n = 15), major complications were seen in 3.8% (n = 4), and mortality rate was 0.9% (n = 1). Conclusion Endovascular treatment is effective in the management of pancreatitis-related bleeding and is associated with low rebleeding rate and low mortality rate.